The Influence Of The Marketing Mix On Consumer Purchase Decision Bagoster Trans Studio Mall Makassar - Andi Dewa Mauraga; Aslinda; Muh. Rizal S; Andi Muhammad Rivai; Maya Kasmita (Business Research and Administration Innovation, 2025)
This study aims to determine how much influence Marketing Mix has on Consumer Purchase Decisions at Bagoster Trans Studio Mall Makassar. This study uses a quantitative method of associative descriptive research type. Data collection techniques used are questionnaires, documentation and observation. The population in this study was 2375 people. The sampling method used was using the Slovin formula, which was narrowed by 96 people. The data obtained from the research results were processed using the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and inferential analysis. Based on the results of the study, it shows that: (1) the influence of marketing mix is in the very high category, and the purchase decision is in the very high category. (2) The correlation coefficient is 0.890 which means that the relationship between Marketing Mix and Purchase Decision is very high. The coefficient of determination obtained is 0.792 or 79.2%, which means that the effect of the Marketing Mix on Purchase Decisions is 79.2% (assuming that other factors are constant)